A Digital Twin Model for Optical Telescope Pointing Systems - Zhenghao Li; Yahui Zhang; Yan He (IEEE Photonics Journal, 2024)
Pointing accuracy, as one of the important indexes to measure the performance of optical tele-scope products, is directly related to the observation quality and efficiency of the telescope, but affected by a variety of complex factors, the timeliness problem of pointing correction affects the smooth progress of the work. In this study, this paper focuses on the error modelling of optical telescope pointing system under limited observation conditions. In this paper, we first explore the changing law of each parameter and the unknown system error. On this basis, assuming that the system is in a stable state, a digital twin modelling model applied to the pointing system of an electro-optical telescope is proposed, which significantly improves the accuracy of the local pointing error correction by means of a limited observing condition: one newly captured star, and simulates and evaluates the feasibility of the twin model by using the experimental data from the external field, which provides the conditions for the evaluation of the maintenance status of the equipment.